FROM WATCHING DRAMA BOX TO WRITING NARRATIVE TEXT: AN EXPERIMENTAL STUDY FOR XII GRADE AT SMAN 1 SELONG - Halimatussakdiyah, Siti; Sri Wahyuni; Astrid Dwimaulani; Ari Prasetyaningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using Drama Box on the narrative writing abilities of twelfth-grade students at SMAN 1 Selong. Purposive sampling was used to choose 31 students for the study, which used a quantitative pre-experimental design with a one-group pre-test and post-test strategy. The Watch, Pause, and Predict method was used in four sessions of the intervention. To ensure assessment consistency, students' written work was evaluated by two raters, and inter-rater reliability testing showed an agreement level of 58.06% for the pre-test, increasing to 67.74% for the post-test. Descriptive statistics, Shapiro-Wilk normality testing, and inferential statistics utilizing the Paired Sample t-Test and N-Gain score computation were used to examine the data gathered from writing assessments. The class mean score increased from 70,64 in the pre-test to 86,77 in the post-test, indicating a notable improvement in students' narrative writing performance. H0 was rejected as a result of the hypothesis test, which produced a t-count of -9,274 and a t-table of 2,045 at a significance level of 3,55×10ˉ10 (p < 0.05). Additionally, the N-Gain score analysis showed an average score of 0.65, which puts it in the moderate group with a 64,73% effectiveness percentage. These findings confirm that the Drama Box learning medium, combined with the Watch, Pause, and Predict technique, has a significant positive impact and serves as an effective alternative learning tool for enhancing students' narrative writing skills, despite being limited by a one-group pre-test and post-test design and a short intervention period.